Effects of entomopathogenic fungi on individuals as well as groups of workers and immatures of atta sexdens rubropilosa leaf-cutting ants - Stefanelli, Luis Eduardo Pontes [UNESP]; Filho, Tarcísio Marcos Macedo Mota [UNESP]; Camargo, Roberto da Silva [UNESP]; de Matos, Carlos Alberto Oliveira [UNESP]; Forti, Luiz Carlos [UNESP] (MDPI, 2021)
In 2009, sulfluramid, the main ingredient in toxic baits for leaf-cutting ant control, was included in Annex B of the Stockholm Convention on Persistent Organic Pollutants. This resulted in interest in the use of entomopathogenic fungi such as Beauveria bassiana and Trichoderma harzianum for leaf-cutting ant control. The efficiency of these fungi in controlling these insects and the way that ants react individually or in group to the biological risks posed by these fungi is poorly understood. For this reason, we assessed the effects of B. bassiana and T. harzianum on Atta sexdens rubropilosa larvae, pupae and workers. Moreover, we investigated whether the number of contaminated individuals within a group has an influence in controlling the spread of fungi among workers. We found that the fungus T. harzianum showed high pathogenicity against A. sexdens rubropilosa larvae and pupae, leading to faster mortality and a survival rates. On the other hand, the fungus B. bassiana was responsible for causing faster worker mortality and lower survival rates. In addition, we observed that an increase in individuals contaminated with B. bassiana or T. harzianum in the group decreases its survival rate. The results support the hypothesis that entomopathogenic fungi are efficient in controlling leaf-cutting ants when contaminated workers are allocated to groups of healthy workers.
Keywords: Beauveria bassiana; Formicidae; Leaf-cutting ants; Sulfluramid; Trichoderma harzianum